Shell Lesions Associated With Emydomyces testavorans Infection in Freshwater Aquatic Turtles. Issue 3 (May 2021) - Woodburn, Daniel B.; Kinsel, Michael J.; Poll, Caryn P.; Langan, Jennifer N.; Haman, Katherine; Gamble, Kathryn C.; Maddox, Carol; Jeon, Albert B.; Wellehan, James F. X.; Ossiboff, Robert J.; Allender, Matthew C.; Terio, Karen A.
A newly described onygenalean fungus, Emydomyces testavorans, has been isolated from ulcerative shell and skin lesions of freshwater aquatic chelonians. To investigate the shell lesions associated with infection and determine if any lesional features were unique to E . testavorans, tissues from turtles housed in zoological institutions ( n = 45) in the United States and free-living turtles ( n = 5) submitted for diagnostic biopsy or necropsy were examined. Free-living turtles were from geographically distinct habitats in Florida ( n = 1) and Washington ( n = 4) at the time of sampling. Histologic shell sections were evaluated for the presence or absence of specific lesional features. Infection with E. testavorans was evaluated in all cases by screening GMS (Grocott-Gomori's methenamine silver)-stained histologic sections for the presence of morphologically consistent fungi and by quantitative PCR (polymerase chain reaction) on representative frozen tissue or formalin-fixed paraffin-embedded sections. Additionally, culture was performed for 15 cases with available fresh/frozen tissue. In total, there were 17 PCR-confirmed E. testavorans cases, 29 cases with morphologically consistent fungi on GMS-stained sections, and 21 cases of shell lesions without histologic or molecular evidence of E. testavorans infection. Epithelial inclusion cysts, defined as cystic structures within the dermis lined by keratinized stratified squamous epithelium and containing necrotic bone and keratin debris, were significantly ( P < .01) associated with E. testavorans infection. Other significantly associated shell lesions included squamous metaplasia, hyperkeratosis, inflammation, and osteonecrosis ( P < .05). This study identified characteristic shell lesions associated with E. testavorans infection. Further studies to prove causality are needed.